A Novel Technique for Fault-Tolerant Control of Single-Phase Induction Motor - Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This research discusses about vector control of single-phase Induction Motor (IM) with two main and auxiliary windings under stator winding open-phase fault based on Indirect Rotor Flux-Oriented Control (IRFOC). Unlike conventional controller which can only be used for single-phase IM with two windings, the proposed technique in this paper can also be used for single-phase IM under open-phase fault. The proposed fault-tolerant drive system in this paper is based on using transformation matrix. Simulations results confirm the validity of the theoretical analysis.